AN EMPIRICAL INVESTIGATION TO ASSESS THE DEBT BURDEN ALONG THE BELT & ROAD INITIATIVE - Murtaza, Sobia; Ali, Dr. Akhtiar (The journal of contemporary issues in business and government, 2021)
The purpose of this study is to provide insight into the impact of expected infrastructure investment under the Belt and Road Initiative (BRI) on the debt burden of countries participating in BRI. As a result of Belt and Road debt lending, national debt in some countries is expected to skyrocket. This paper assesses the medium-term debt vulnerability of BRI investments among participant countries. BRI investment debt loans will be fully repaid in the medium term (2012-2026), but the impact on the full growth of BRI-related infrastructure will not be fully exploited. BRI is expected to drive overall growth and nearly one-third of rated BRI recipients will face an increased debt burden.